(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The article deals with the problems of university teaching. It analyses the possibility to improve the quality of traditional university teaching by introducing enterprise competencies and making them one of the outcomes of learning. The authors present the results of the research that has been carried out using a method of a questionnaire at the Lithuanian Academy of Physical Education. The aim of the study was to investigate the development of enterprise competencies in undergraduate population. The research was conducted in the Faculty of Sports Technologies and Tourism at the Lithuanian Academy of Physical Education. The randomly selected sample consisted of 131 second and fourth year students of sports and tourism management. The data obtained helped to draw the following conclusions: traditional teaching methods prevail at the Lithuanian Academy of Physical Education; in the process of university studies students pay greater attention to theoretical knowledge than to the acquisition of practical skills; the second and the fourth year students of sports and tourism management lack systematic development of enterprise competencies in the process of teaching. In the scale of importance, the most appreciated enterprise competencies are as follows: ability to communicate, computer literacy, knowledge of one’s capabilities, ability to work in a team; accordingly, the least appreciated enterprise competencies are as follows: ability to seek and to act on new opportunities, ability to analyse statistical data, ability to eliminate stressors, managing personal stress and stressful situations. Keywords: quality, university teaching, enterprise competencies.